2014
DOI: 10.5194/bg-11-2443-2014
|View full text |Cite
|
Sign up to set email alerts
|

Long-term trend of CO<sub>2</sub> and ocean acidification in the surface water of the Ulleung Basin, the East/Japan Sea inferred from the underway observational data

Abstract: Abstract. Anthropogenic carbon is responsible for both global warming and ocean acidification. Efforts are underway to understand the role of ocean in a high CO2 world on a global context. However, marginal seas received little attention despite their significant contribution to biogeochemical cycles. Here we report the CO2 increase and ocean acidification in the surface waters of the Ulleung Basin (UB) of the East/Japan Sea, and possible causes are discussed. Fourteen observations of surface fCO2 were made in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 65 publications
1
22
0
2
Order By: Relevance
“…Kim et al (2014) reported the repeat observations in the Ulleung Basin. Chou et al (2013a) contrasted the different seasonal patterns of pCO 2 in the ECS in the 1990s and the 2000s.…”
Section: Increasing Atmospheric Co 2 and Changing Carbonate Chemistrymentioning
confidence: 68%
See 1 more Smart Citation
“…Kim et al (2014) reported the repeat observations in the Ulleung Basin. Chou et al (2013a) contrasted the different seasonal patterns of pCO 2 in the ECS in the 1990s and the 2000s.…”
Section: Increasing Atmospheric Co 2 and Changing Carbonate Chemistrymentioning
confidence: 68%
“…The observed pCO 2 in the Ulleung Basin yield a rather large increasing trend with very large uncertainty due to the strong seasonal variation (Table 2). Using a sophisticated data processing technique to delineate the seasonal variation, Kim et al (2014) obtained a moderately strong trend of 2.7 ± 1.1 µatm yr −1 . For the SCS, we have constructed a time series from observations from the South East Asia Time-Series Study (SEATS) station (Tseng et al, 2007) and observations from Domain B in the northern SCS, which covers the SEATS station (Zhai et al, 2013).…”
Section: Increasing Atmospheric Co 2 and Changing Carbonate Chemistrymentioning
confidence: 99%
“…improving our understanding of the regional carbon cycle. However, there have been only a few studies analyzing the carbon dioxide in the East Sea using in situ data [20,23,30]. Park et al [32] constructed a neural network model to estimate pCO 2 in the East Sea based on satellite-derived SST and Chl-a and in situ pCO 2 data from 2003 to 2012.…”
Section: Introductionmentioning
confidence: 99%
“…대륙주변해는 대기, 해양, 대륙을 잇는 주요 탄소 저장고로서 (Omar et al, 2007), Tsunogai et al(1999) (Takahashi et al, 2002;Takahashi et al, 2009;Friedrich and Oschlies, 2009b) 동 해에서 표층 pCO 2 를 계산하는 모델 구축 연구도 진행되어 왔다 (Oh et al, 1999;Kang, 1999;Choi et al, 2011;Kim et al, 2014 (Lefèvre et al, 2005;Friedrich and Oschlies, 2009a;Telszewski et al, 2009;Jo et al, 2012;Landschützer et al, 2013). 신경망 모델은 모델 디자인 과정에서 입력자료와 결과값 사이 의 비선형적인 관계를 스스로 만들어 낼 수 있다.…”
unclassified
“…이것은 수온이 비교적 낮은 봄철에는 울릉분지의 pCO 2 도 낮은 경향을 보이며 chlorophyll에 의한 pCO 2 변동성이 가장 크게 나타나는 것으로 해석할 수 있다 . 울릉분지는 계절에 따라 SST, chlorophyll과 pCO 2 의 관계가 다르게 나타나는 것으로 알려져 있으며 연직혼합에 의해 수온이 낮고 pCO 2 가 풍부한 물이 표층으로 올라오게 되면서 수온이 낮고 pCO 2 가 높은 상태를 보일 수 있다 (Oh et al, 1999;Choi et al, 2011;Choi et al, 2012;Kim et al, 2014 Table 2). 반면 연평균 pCO 2 의 직선 회귀로 구한 연간 pCO 2 증가율은 0.8 μatm이다 (Fig.…”
unclassified